Efeitos da acupuntura manual e da eletroacupuntura sobre o estresse oxidativo e a inflamação em modelo experimental de retalhos cutâneos randomizados em ratos - Lima, Lorena Picanço de (2011)
Ischemia of the skin flaps increases the morbidity in surgical reconstruction procedures. Injuries resulting from the interruption or reduction of blood flow (ischemia) and are exacerbated by the reintroduction of oxygen-rich blood (reperfusion). Acupuncture (AC) promotes the stimulation of specific body points (acupoints) in order to achieve a therapeutic or homeostatic effect. Electroacupuncture (EA) is the application of electric current of low intensity and variable frequency through the needle inserted into specific acupoints previously. The choice of waveform, frequency and discharge intensity define the type of effect that will be reached. Whereas some published studies have demonstrated the protective effects of AC/EA in the preservation of skin flaps, this study aimed to investigate the effects of AC/EA in inflammation and oxidative stress in randomized skin flaps in rats. Forty rats were used in the study. Thirty-two animals underwent dorsal flap construction (8 x 2.5cm) and then were distributed randomly into 4 groups (n = 8): G-2 (surgical trauma), G-3 (Acupuncture), G -4 (2 Hz EA), G-5 (EA 100 Hz). The remaining 8 rats served as baseline control (G-1). All rats were anesthetized intraperitoneally with ketamine (90mg/kg) + xylazine (10mg/kg) on days 1, 3 and 7. In day 1 stainless steel needles were introduced in DM-14 [Dazhui], DM-2 [Yaoshu] and F-13 [Zhangmen] acupoints bilaterally in G3 rats.The acupoints are located, respectively, on the cranial, caudal edges and near the lateral edge of the skin flap. In G4, after insertion of needles, EA was applied (3Hz, 10 mA) for 30 minutes. The procedures were repeated on days 3 and 7. In G5 a frequency of 100Hz was used. Blood and skin samples were collected at the end of procedures (AC/AE) in groups G3, G4, G5, and after 30 minutes of anesthesia in G1/G2 rats for myeloperoxidase (MPO), malonaldehyde (MDA) and glutathione ( GSH) assays. The results were compared using the t test for unpaired samples. Skin MPO activity decreased significantly in G3 rats (6.41±1.39 vs. 3.11±2.80, p<0.001). There was also a significant decrease (6.41±1.39 vs. 1.19±0.39) of MPO activity with EA (3 Hz) and 100 Hz (6.41±vs 1.39±0.19) compared with G2. Plasma (6.56±1.32 vs.21.48±4.40) and tissue (54.15±3.10 vs. 180.50±10.35) GSH levels increased significantly in G3 rats. A significant increase in plasma and tissue GSH concentrations ocurred in G4/G5 rats. MDA levels increased significantly in groups G4/G5. Considering these results it is concluded that both AC/EA, applied to healthy rats, attenuate skin inflammatory response and reduce systemic and local oxidative stress, promoting an increase in plasma and tissue concentrations of GSH. On the other hand, EA has pro-peroxidative effect in plasma and skin of healthy rats subjected to surgical stress.